El derecho de resarcimiento del daño sufrido por las víctimas de delitos y el código procesal penal peruano - Mori León, Jhuly (2014)
This research has examined the right to compensation for damage suffered as a victim of the offense in the New Criminal Procedure Code of Peru, in order to identify the reasons why this right is violated. We analyzed sections 58, 59, 60, 62, 64, 92, 93 and 94 of Chapter IV of the Penal Code concerning the stay of execution of sentence, Articles 94, 95, 96, 98, 100, 101, 102, 104, 105, 488 and 489 of the Criminal Procedure Code. It has compared the criminal procedural legislation Costa Rica, Bolivia, Chile, Colombia, Guatemala with Peruvian law. The views of prosecutors and criminal judges and victims gathered in two surveys were taken into account. 150 has been revised tax folders in the implementation phase of various crimes in the District Attorney La Libertad, Peru. We conclude that: i ) in the New Criminal Procedure Code, victims of crime are violated his right to compensation for damage suffered as a result of a crime, lack regulations, minimum sentence, extinction of civil damages and limited use precautionary measures, ii ) in comparative law, for civil damages, there is three ways to enforce, such civil action is pending outside the criminal process and through the box repairs, iii ) victims of crime only object of criminal proceedings and not subject the same as they are used as evidence only to achieve a "successful" research for the Prosecutor or a conviction that generates statistics for the Judiciary, iv ) there are mechanisms that guarantee payment of civil damages, as precautionary measures but are often not enforced.